Enhancing Main Idea Comprehension in TOEFL Reading through Guided Reading Strategies: A Study at SMK Sasmita Jaya 2 - Meylinda, Linda; Erviana, Ridha Ikhva (Doctoral Program of Social Science Pasundan University, 2025)
This study aims to improve students’ ability to identify the main idea in reading comprehension for the TOEFL test at SMK Sasmita Jaya 2 through guided learning using strategic reading techniques. Many students struggle to find the main idea in English texts, necessitating targeted instructional support. The intervention lasted four weeks, applying a collaborative approach that emphasized skimming, scanning, and inference strategies. Seven students who had difficulty with main idea comprehension participated. Data were collected via pre- and post-tests, observational analysis, and in-depth interviews focusing on competence and attitude changes. Results showed significant progress, with average scores increasing from 55 to 72. The intervention also enhanced student motivation and self-confidence in preparation for the TOEFL exam. The study is based on Vygotsky’s Social Constructivist Theory (1978), which highlights the role of social interaction and scaffolding in learning. Guided reading strategies acted as scaffolding to connect students' current skills to desired competencies, facilitating reading comprehension development. The findings suggest that guided strategy-based reading instruction effectively improves comprehension and positively affects learners’ psychological aspects. This research supports creating English learning models for vocational schools, particularly to prepare for international standardized tests, and offers potential for adapting this model to other educational contexts aiming to improve reading skills. Overall, the study contributes to initiatives aimed at enhancing English proficiency among vocational students in Indonesia.